Implementasi Pendidikan Karakter di SDN-1 Panarung Kota Palangka Raya - Supardi Supardi (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2013)
This study aims to find out and find data in the implementation of tasks in the students at SDN-1 Panarung, Kelurahan Pahandut, Sebangau District, Kota Palangka Raya.The method used in this study is a qualitative method which generally uses techniques to collect data, interview to communicate with informants or objects of research, and documentary studies (documentation) to collect data sourced from archives that are inside and outside the school. On the basis of this concept is the technique used by the data above in this study. Research results: Principals and Teachers at SDN-1 Panarung Palangka Raya are very interested in applying character education where schools provide facilities and infrastructure in the form of syllabi, lesson plans, and books for students in the learning process to facilitate teachers and since the introduction of character education can improve learning outcomes or student achievement. From the results of the study can be used to determine the condition of the students who are educated in education and learning.